Size does not matter: Diseconomies of scale in the mutual fund industry revisited - Phillips, Blake; Pukthuanthong, Kuntara; Rau, P. Raghavendra (Journal of Banking & Finance, 2018)
The academic literature has found mixed evidence that fund size is negatively related to performance. One reason for the lack of consensus may be that the fund size and performance relation is endogenous. In this paper, we identify a set of instrumental variables that influence fund size but are unrelated to expected fund performance. Using this specification, we show that fund size does not appear to affect fund performance.